Agricultural dust explosions in 2000 - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
There were eight dust explosions reported in the U.S. in 2000 according to Robert W. Schoeff, Professor Emeritus, Kansas State University, and Mavis Rogers, FGIS-USDA. This compares to 7 in 1999 and a ten year average of 12.1 explosions.
Keywords: Grain dust; Dust explosions